The Hypoactivity Associated with the Repeated Exposure to Atrazine Is Related to Decreases in the Specific Binding to D1-DA Receptors in the Striatum of Rats - José Abraham Márquez-Ramos; Isela Hernández-Plata; Mauricio Díaz-Muñoz; Verónica M. Rodríguez (Journal of Toxicology, 2017)
The herbicide atrazine (ATR) has a potential toxic effect on the neuronal circuits of the brain, specifically on two major dopaminergic pathways: the nigrostriatal and mesolimbic circuits. In this work, we repeatedly exposed adult male Sprague-Dawley rats to 6 injections of 100 mg ATR/kg of body weight (for two weeks) and one saline injection two days after ATR administration. Locomotor activity was assessed for 15 minutes and/or 2 hours after ATR or saline injection and 2 months after the final ATR administration. The specific binding of [3H]-SCH23390 to D1-DA receptors and that of [3H]-Spiperone to D2-DA receptors in the dorsal and ventral striatum were assessed 2 days and 2 months after ATR treatment. ATR administration resulted in immediate, short- and long-term hypoactivity and reduced specific binding of [3H]-SCH23390 in the dorsal striatum of rats evaluated 2 months after the last ATR injection. The specific binding of [3H]-SCH23390 in the ventral striatum and the specific binding of [3H]-Spiperone in the dorsal and ventral striatum remained unchanged at 2 days or 2 months after ATR treatment. These results, together with previous findings of our group, indicate that the nigrostriatal system is a preferential target for ATR exposure.